STEM-13. HYPOXIC INDUCTION OF VASORIN MEDIATES GLIOMA STEM CELL-ENDOTHELIAL CELL INTERACTIONS IN THE PERIVASCULAR NICHE. (5th November 2018) - Yu, Jennifer; Yu, Xingjiang; Burrows, Amy; Bao, Shideng
Abstract: Glioma stem-like cells (GSCs) have been recognized to play an important role in tumor progression. GSCs are highly resistant to radiation and chemotherapy and have a high capacity to self-renew and differentiate into multiple lineages. GSCs preferentially reside within niches including the hypoxic and perivascular niches that help to support their undifferentiated state. Interactions between GSCs and different cell types in these niches, including endothelial cells, help to maintain GSCs and facilitate tumor migration, invasion and angiogenesis. We previously identified that the transmembrane protein Vasorin (VASN) is a critical node in GSC maintenance. Little is known about this protein (< 20 papers), but we have found that VASN is overexpressed in about 80% of GBM and is associated with poor prognosis. VASN is preferentially induced in GSCs in hypoxia and binds Notch1 to stabilize it at the cell membrane. This interaction effectively functions as a switch to amplify Notch signaling in GSCs in hypoxia to promote their survival. We now build upon these studies and find that VASN is expressed in GSCs not just in the hypoxic niche but also the perivascular niche. GSCs are abundant in the perivascular niche and endothelial cells can provide Notch ligands that help to maintain GSCs self-renewal properties. We have found that VASN is frequently expressed in hypoxic, CD44+ and Olig2+ tumor cells in the perivascular niche in GBM, and that VASN is expressed in a subset of tumor-associated endothelial cells. Our data suggest that reciprocal Notch signaling mediated by VASN between endothelial cells and GSCs in the perivascular niche helps to maintain GSCs. These data suggest that VASN may also play an important role in perivascular niche interactions between GSCs and endothelial cells through Notch signaling.